Follow-Up of the Bank of Algeria to the Principles of the Basel Committee through the Legislation of Internal Control Systems for enhancing governance for banking organisations - Boutora, Fadila; Smaili, Nawfel (Milev Journal of Research and Studies, 2019)
The Study aims at Highlighting the Development of the Legislation of the Bank of Algeria for Internal Control Systems, where themes revolved around the most important Legislation to contribute to keep up its legislation with the decisions of the Basel Committee on Banking Supervision to create a Banking environment in line with international standards of banking business. This Study Highlights the results of the Bank Algeria harmonize Legislation in the field of Internal Control with desire and determination to keep up its Legislation with the decisions of the International Committee of the Basel Banking Supervision, which world boost confidence in the Internal environment of the Banks , which also reflected on the Banking Performance as a whole effectively.